وجهة نظر سكان قرية عورتا اتجاه ظاهرة الزواج المبكر - قواريق, لين فواز (My University, 2017)
الملخص يتناول هذا البحث وجهات نظر سكان قرية عورتا تجاه ظاهرة الزواج المبكر (دراسة ميدانية)، حيث كان الهدف منه تنبع من انه تقوم على أساس قياس الاتجاهات أي حسب خبرة الفرد ووجهة نظره، والتعرف على الإيجابيات والسلبيات التي قد تؤثر على الفتاه، والكشف عن الاثار التي يتركها الزواج المبكر للفتيات في عمليه التنمية الاجتماعية، ولتحقيق أهداف البحث تم اجراء الاستطلاع النهائي وذلك من خلال استخدام وسيلة جمع البيانات الاستمارة وبلغ عددها (100) استمارة ، ووزعت على (50) ذكر و (50) انثى، من مختلف الاعمار وبطريقه عشوائية ، واستخدام برنامج التحليل الاحصائي spss لتفريغ الاستمارات، كما استخدمت الباحثة المقابلات الشخصية لمجموعة من النساء اللواتي تزوجن في سن مبكرة للكشفعن أهم الاثار الذي تركها ، وانتهت الباحثة بالخروج بمجموعة من النتائج والتوصيات منها : وضحت الدراسة معرفة اتجاهات افراد العينة في العمر المثالي لزواج الذكور والاناث ، فقد تبين ان متوسط العمر المثالي لزواج الذكور (25-29) سنة، كما بينت الدراسة أيضا أن العمر عند الزواج الأول لمن سبق لهم الزواج ، الذكور (24-26) سنه والاناث (18-20)، وهذا يتعارض مع رأي الاناث في العمر المثالي لزواج الاناث، والسبب في ذلك ان الفتيات ادركن ان العمر الذي تزوجن فيه هو مبكرا فقمن باختيار اعمار اكبر من هذه المتوسطات، ووضحت الدراسة العمر المبكر لزواج الذكور والاناث من وجهة نظر افراد العينة (15-19) سنة لكلا الجنسين لان هذه الاعمار يمر كلا الجنسين بمرحله المراهقة وما يصاحبها من اضطرابات نفسية وعاطفية، مما يكونوا غير قادرين على اتخاذ قرارتهم المستقبلية. أمامن التوصيات: توفير فرص عمل للمتزوجين هذا بدوره يسهم في تخفيف البطالة وتحسين من مستوياتهم المعيشية، الابتعاد بقدر كبير عن زواج الأقارب وهذه كانت اراء افراد العينة، لما له من اثار سلبيه في نقل الامراض الوراثية وإنجاب أطفال ذوي إعاقة، ونشوء الخلافات الزوجية الأسرية ونتاج هذا الطلاق الذي يؤدي الى حالات الاكتئاب لدى الفتيات. Abstract This research is about the opinions of the residents of Awarta village towards the phenomenon of early marriage in order to face early marriage (field study), The purpose of this study is to be based on measuring the trends according to the individual experiences and their point of view,by identifying the advantages and disadvantages that may affect the girls, and uncovering the effects of early marriage for girls in the process of social development . In order to achieve the objectives of the research, the final survey was conducted through the use of the data collection forms, and the number of forms reached (100) , the forms were distributed to (50) males and (50) females, of different ages and in a random way, so We have emptied the form data by using the statistical analysis program (SPSS) , The researcher also used interviews with a group of women who married at early age to uncover the most important effects that early marriage left , so the researcher ended up with a set of Results and Recommendations , including: The study explained the attitudes of sample members in the ideal age for marriage between males and females , where it shows that the average age of marriage for males (25-29) years, also it showed that the age at first marriage of those who had previously married, for males(24-26) years and for females (18-20) , and this contradicts the view of females in the ideal age of female marriage , the reason for this is that the girls realized that the age which they married at is early, so they chose a higher age than these averages, the study also showed that the early age of marriage between males and females from the point of view sample is (15-19) years for both genders , because these ages both genders passes through adolescence and accompanying psychological and emotional disorders where they are unable to make their future decisions . Among the recommendations: First of all, Providing employment opportunities for married couples in turn contributes to reducing unemployment and improving their living standards, Second and last, Avoid the marriage of relatives as much as possible , these were the opinions of the sample members , because of it's negative effects in the transmission of genetic diseases and giving birth of children with disabilities , also the emergence of family marital differences and the result of this is to divorce, which leads to cases of depression in girls
The View of the Residents of the village of Awarta Towards the Phenomenon of Early Marriage
Keywords: عورتا، الزواج المبكر، التنمية الاجتماعية.